Pengaruh Lingkungan Kerja Non Fisik Dan Work Engagement Terhadap Kepuasan Kerja Karyawan Pada PT Tampah Boga Nusantara Kota Tangerang Selatan - Fahrani Al Fareza Hizrah Lutvhia; Fahmi Susanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstrak. This study aims to determine the influence of non-physical work environment and work engagement on employee job satisfaction at PT Tampah Boga Nusantara in South Tangerang City. This research method used quantitative research methods. The data collection method used was a questionnaire survey. The population used in this study consisted of 80 employees. The sampling technique used saturated sampling, and obtained a sample of 80 respondents. Data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, correlation coefficient, simple linear regression, multiple linear regression, coefficient of determination, and hypothesis testing. The hypothesis testing partially on the variable of non-physical environment (X1) obtained a calculated t-value > table t-value (12,677 > 1,991), which is also reinforced by a significance value of 0.000 < 0.05. This means that non-physical environment (X1) has a significant effect on employee job satisfaction. Partial hypothesis testing of the work engagement variable (X2) obtained a calculated t-value > table t-value (12,625 > 1,991), which is also reinforced by a significance value of 0.000 < 0.05. This means that the work engagement (X2) has a significant effect on employee job satisfaction. Simultaneous hypothesis testing obtained a calculated t-value > table t-value (160,713  > 3.120), which is also reinforced by a significance value of 0.000 < 0.05. Thus, it can be said that the non-physical work environment and work engagement simultaneously have a significant effect on employee job satisfaction. The coefficient of determination obtained an R Square value of 0.671, meaning the non-physical work environment and work engagement together contribute a 67.1% influence on employee job satisfaction.